Beetles of Peru: a survey of the Families. Eucnemidae Eschscholtz, 1829 - Otto, Robert L. (2017)
A checklist of the eucnemid beetles of Peru is presented, based on a literature survey and identification of specimens from two museums. The Peruvian fauna comprises ~107 species in 30 genera from eight tribes and three subfamilies. Nine genera are newly recorded for Peru. They include: Xylophilus Mannerheim 1823, Temnillus Bonvouloir 1871, Gastraulacus Guérin-Méneville 1843, Somahenecus Cobos 1964, Silveriola Cobos 1956, Onichodon Newman 1838, Cladus Bonvouloir 1872, Thambus Bonvouloir 1871 and Neomathion Fleutiaux 1930. Fifty-eight species are newly recorded for Peru. A familial diagnosis as well as notes on eucnemid habitat, collecting methods, and biology are provided. This contribution is part of the ‘Beetles of Peru’ project.